The complement system in human pregnancy and preeclampsia - Kumar, Vijay; Stewart, John H. (Frontiers in Immunology, 2025)
Human pregnancy is a complex condition that poses significant challenges for women due to the necessity of a uterus for key processes such as fertilization, embryo implantation, fetal development, and childbirth. These processes are governed by immunological factors and accompanied by various physiological changes. For a successful pregnancy, maternal immune reprogramming is crucial because the developing embryo is considered a semi-allograft. Any immunological alteration during pregnancy induces recurrent pregnancy loss and other fetal–maternal health issues, including preeclampsia. However, despite advances in reproductive immunology, the exact immunopathogenesis of preeclampsia remains unclear. The complement system (CS) is an evolutionarily ancient and critical innate immune component that plays a significant role in maintaining immune homeostasis. The current article discusses the critical role of the CS in human pregnancy and how its dysregulation predisposes pregnant women to preeclampsia. The article introduces the concept of the Th1 to Th2 immunological shift as a prerequisite for a successful pregnancy and the evolution of decidualization via transposable elements, which recruit genes responsible for the process in the endometrium. The immune system plays a critical role in decidualization. The second section discusses the CS signaling pathway, its negative regulators, and the roles of the C3a/C3aR and C5a/C5aR1/C5aR2 or C5L2 axis in immune homeostasis. The third section elaborates on the role of the CS in the establishment of human pregnancy, such as fertilization, implantation, and fetal development. The fourth section describes maternal CS signaling alteration during successful human pregnancy. The fifth section describes the role of CS signaling in preeclampsia, including its systemic and local (placental) alterations and the responsible mechanisms. The article closes with future perspectives and a summary that describes important complement-based approaches for diagnosing and treating preeclampsia.